Specific Aspects of the Ancient Material Culture of Central Asia - Isamiddinov Muhammad Hasanovich (Genius Journals, 2023)
In the first centuries AD, there was a large Kushan Empire in the southern regions of Central Asia, the Indian Peninsula, Afghanistan, southern Uzbekistan, and southern Tajikistan, and the Parthian Empire in its western parts, Iran, Turkmenistan, and the Black Sea region. they had Hellenistic culture, and in the north of these countries, a union of large semi-peasant, semi-herding states – “Hellenized culture” was formed in the territories of the Kang state.
Keywords: Kushan state; Parthia; Kang; Hellenism